Revisiting the Effect of R&D intensity on innovation Performance: An Instrument Variable Approach - Darfo-Oduro, Raymond Kwame Adane (Academic Conferences and Publishing International Limited, 2023)
The literature on innovation performance makes clear the important role of R&D in innovation performance. Studies that have investigated this relationship have generally assessed the effect of R&D investment on innovation performance. It is important to note that innovation performance and R&D investment are known to be closely associated with the possibility of reverse causality. Regressing innovation performance on R&D expenditure therefore poses an important statistical challenge of endogeneity. In the presence of endogeneity regression parameter estimates are biased and inconsistent and therefore hypothesis testing may be misleading. Using data from different sectors of OECD economies sourced from the OECD data base, instrumental variable analysis is conducted through a two stage least square using the number of R&D personnel as instrument. Again, the literature assumes that innovation is an increasing function of R&D. However, considering R&D is combined with other factors, some of which are fixed, the possibility that R&D will experience diminishing returns cannot be overlooked. This means that the dominant linear relationship authors specify in these studies may not be wholly accurate. We captured this effect by modeling a quadratic relationship to reflect the diminishing returns to innovation performance. The findings of the study show that the number of R&D persons exhibit a nonlinear inverted U-shaped relationship with innovation performance. The policy implication of the findings of the study is that R&D activities must be commensurate with the size of other organizational factors to ensure that changes in R&D activities solicit a favourable response from innovation performance.
Přehodnocení vlivu intenzity výzkumu a vývoje na výkonnost inovací
Keywords: innovation performance; instrumental variable; OLS regression; R&D intensity; inovační výkonnost; instrumentální proměnná; OLS regrese; intenzita výzkumu a vývoje